Learning to Prosper by Wrestling and by Negotiation: Jacob and Esau in Contemporary African Pentecostal Hermeneutics - Asamoah-Gyadu, J. Kwabena (Journal of Pentecostal Theology, 2012)
Pentecostalism in Africa has evolved as different streams characterized by particular modes of articulating the Christian message. The older independent churches were known for their emphasis on healing and prophecy and the classical Pentecostals talked much about speaking in tongues and holiness. Although these themes are present in contemporary Pentecostal discourse the new churches are best known for their messages of empowerment and prosperity that are meant to address the aspirations of Africa's upwardly mobile youth. Using the writings of two of the movements most influential leaders from Ghana, this article discusses the ways in which the story of the Patriarchs, especially Jacob, has been reinterpreted to fit into the message of upward mobility and the principles that are meant to lead up to it. It is argued here that although the authors did not intend to misapply Scripture, by reinterpreting the schemes of Jacob in terms of the principles of success, they fail to take account of the element of 'grace' which is able to turn the worst of sinners into saints. Jacob did not succeed because he applied the principles of success but because God touched him with his grace during the time of wrestling with the angel.
Paid
Keywords: AFRICA; Agriculture – Religious aspects; Anaba; Joseph Eastwood; Bible. Genesis – Criticism; interpretation; Bible. Genesis 25-36; CHRISTIANITY; Decision making (Ethics); Economics and Christianity; Ends and means; Esau; Esau; (Biblical figure); Fraud; God – Activity; Grace – Biblical teaching; HERMENEUTICS; Hunting – Religious aspects; INDEPENDENT churches; Jacob; Jacob; (Biblical patriarch); Negotiation; Otabil; Mensa; PENTECOSTALISM; PENTECOSTALS; PROPHECY; Pastoral theology – Pentecostal churches; Peer reviewed; Pentecostal churches – Africa; Pentecostalism; Power (Theology); Preaching; Pentecostal; Prosperity theology; Tithes; charismatic; grace; hermeneutics; prosperity gospel